The Effects Product Placement within Songs and Music Videos Can Have on Consumers - Nightingale, Bethany (2012)
The qualitative study explores the effects product placement can have on consumers and how a consumers perception can change once exposed to product placement. The past research has mainly been focused on its use in films and in television, so this studies focuses on another popular mass communication method - songs. This study also investigates the use of product placement in music videos and whether there is a connection in the consumers mind between the two. The findings indicate that there are various ways in which product placement in music affects consumers. They have opinions on its prominence, the amount of times it’s repeated and the likelihood of them buying that particular product. Also discussed were the participants’ attitudes towards the use of product placement, the attitude towards the artist, genre and brand and whether they believed it to be ethical. The findings show that there is no clear answer, with each participant responding differently. This study only goes so far, and is used to encourage others to explore this topic area.